A Location Privacy Extension for DVB-RCS - Aggelis, Aggelis; Sarris, Emmanuel T.; Katos, Vasilios (Společnost pro radioelektronické inženýrství, 2011)
In this paper we studied the DVB-RCS (Return Channel through Satellite) standard from a privacy perspective and proposed an approach to incorporate a location privacy enhancing mechanism into the standard. Offering location based privacy in DVB-RCS communication is a challenge as the location of a satellite terminal must be revealed to the network operator of the DVB-RCS network for technical and administrative reasons. We proposed an approach of cloaking the location by intentionally compromising its accuracy whilst maintaining the operability and integrity of the communications system. In addition we implemented a proof of concept technique utilizing the theoretical findings of this work on a real DVB-RCS system, presenting the methodology along with the tools used and the experimental results.
Keywords: DVB-RCS security; location privacy; satellite communications; data cloaking; spatial accuracy